(untitled) (International Journal of Language, Literacy and Translation, 2025)
Mixed-identity individuals often encounter many problems on questions of their identity, belonging, and other forms of multiracialism. A mixed-identity individual is often seen as a lonely or isolated individual. Two well-known novels focus on this dimension – D. Defoe’s The Fortunes and Misfortunes of the Famous Moll Flanders (1996) and C. Rajendra’s No Bed of Roses: The Rose Chan Story (2013). The two authors’ emphasized portrayal of their heroines’ problematized hybrid identities and resultant complex struggles are the focal points of this study. The broad aim was to analyze the explicit and implicit metatextualities of such identities (via social hybridity) in these texts, within the scope of constructing an identity in terms of (dis)inclination towards multiracial marriages. The study is grounded in Genette’s (1997, 1992) theory of intertextuality; with respect to explicit metatextuality, the researchers focused on the strategies of interpretation and negation, whereas ironies and parodies were tackled as implicit metatextuality. Intertextuality is an integral part of textology and textual analysis of both literary and non-literary works. It is a framework to study text constructions and internal relations between texts as well as interactions between authors and readers. On the whole, the results demonstrate that irrespective of the novelists’ backgrounds (Defoe being English and Rajendra a Malaysian) as well as the novels’ settings (Moll’s story was set in London, UK, while Rose’s was set in Penang, Malaysia), there are clear instances of the shaping of (dis)inclination for hybrid marriages and their resultant identities, with Rajendra’s work exhibiting more of such identities than Defoe’s. This study and its findings are of significance to scholars engaged in literary research, and might potentially facilitate students’ understanding of Western and Eastern comparative literature in terms of identity construction and mutual communication in diverse societies.